HYGIENIC AND TOXIC SAFETY OF ANTISEPTICS USED IN DENTAL PROCEDURES - Baxodurov Botirxon Nodir oʻgʻli; Norova Mavjuda Bakhodurovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Annotation: Antiseptics are widely used in dentistry for infection control during various procedures, including surgical interventions, cavity preparation, root canal treatment, and oral hygiene maintenance. While antiseptic agents such as chlorhexidine, hydrogen peroxide, povidone-iodine, and sodium hypochlorite have proven antimicrobial effectiveness, their hygienic safety and potential toxic effects on oral tissues and systemic health must be carefully considered. This article reviews commonly used dental antiseptics, their mechanisms of action, potential cytotoxicity, allergenicity, and mucosal tolerance. Emphasis is placed on balancing antimicrobial efficacy with patient safety, particularly in pediatric and immunocompromised populations. Recommendations for the safe clinical application of these agents are also discussed.